ANALYSIS OF THE COSTS AND BENEFITS OF A COMMON CURRENCY FOR THE SECOND WEST AFRICAN MONETARY ZONE (2012)
The second West African Monetary Zone (WAMZ), comprising The Gambia, Ghana, Guinea, Nigeria and Sierra Leone, was initiated in 1999 to fast-track the common monetary policy objective of the Economic Community of West African States (ECOWAS). However, uncertainties about the economic implications of the policy have been major obstacles to regional integration. Economists and policymakers are yet to agree on the potential costs and benefits of a common currency. Available empirical studies on WAMZ focused separately on the elements of costs and benefits of monetary union, which makes them limited in scope. This study, therefore, offered an integrated analysis of the costs and benefits of a common currency in WAMZ spanning 1980 to 2009. A two-step methodological procedure, based on the Optimum Currency Area (OCA) and the New Optimum Currency Area (NOCA) frameworks, were used to estimate the costs and benefits of monetary union in WAMZ. First, behavioural models, capturing the elements of costs (asymmetric shocks, loss of seigniorage and fiscal policy distortion) and benefits (trade creation, financial integration effects and policy coordination gains), were estimated with the Vector Auto-regression (VAR), Error Correction Model (ECM) for each of the sampled countries and panel estimation techniques for the group. Second, weighted composite indices were constructed for the costs and benefits indicators using the parameter estimates obtained from the various estimation techniques. The VAR impulse response and forecast error methods were employed to estimate countries‟ response to shocks. Robustness tests, including data calibration for the net-benefit using a money metric baseline and ranking, were carried out to permit comparison of results among countries. Fiscal policy distortion and loss of seigniorage were the main cost indicators of monetary union in the zone rather than asymmetric shocks. The share of fiscal policy distortion stood at 72.4%, while loss of seigniorage contributed 18.4% to the costs of monetary union. Ghana recorded the highest costs of 36.0% for fiscal policy distortion and 65.0% for loss of seigniorage in the zone. The Gambia had the lowest seigniorage cost of 8.0%. Considerable variations existed among Sierra Leone, The Gambia and Nigeria as fiscal policy distortion accounted for 30.0%, 22.0% and 12.0%, respectively. Trade creation shared 89.0% of the total benefits for the zone. Policy coordination gains had the lowest share of 1.6% for the region. Trade creation gains ranged between 41.0% and 3.0% among the countries with Sierra Leone and Nigeria sharing the highest UNIVERSITY OF IBADAN LIBRARY iii and lowest gains, respectively. The net-benefit of monetary union for the zone was potentially high with substantial variations among members. Sierra Leone and Nigeria had the highest and lowest net-benefit respectively from the ranking scale. Trade creation accounted for a substantial proportion of the potential benefits of common currency in WAMZ. However, fiscal policy distortion constitutes serious policy challenge to monetary union in the zone. Dealing with this challenge may require in the short-run, systematic macroeconomic adjustments to improve fiscal-monetary policy interactions in order to enhance the benefits of monetary union in the zone. Key words: Optimum Currency Area, Behavioural models, Seigniorage, Fiscal policy distortion, Asymmetric shocks. Word count: 489